Андропов и Карелия - Labudin, Alexander; Kirjanen, Alexander; Samodurov, Alexander (Administrative Consulting, 2025)
The main events of the eminent statesman Juriy Andropov's ruling in Karelian-Finnish SSR (1940-1951) are discussed in this article. The decisions of J.Andropov and other Karelian-Finnish leaders (mainly G.Kuprijanov - the first secretary of CK CP KF SSR at that time), directed to the defense of interests of Karelians, Vepses, Finns are analysed also. The problem of the repatriation of Ingermanland Finns to Karelian-Finnish SSR is discussed too. This people were repressed during and immediately after the Second World War according of far-fetched charges with a crime. This problem is discussed in connection with difficult and tragic history of Ingermanland Finns people. The authors draw some actual conclusions for temporary state policy.